Implementation Of Universal Precaution Policy On Class I Nurses In Hospital X - Ika Rachmawati; Yennike Tri Herawati; Reni Reni Indrayani; Dodi Wijaya (Nursing and Health Sciences Journal (NHSJ), 2022)
Universal precaution is a strategy to protect health care workers to prevent the transmission of infectious diseases in all health facilities. The latest data on HAIs at Hospital X shows that the highest number of HAIs occurs in class I inpatient rooms at 3.8%. This study aims to describe the implementation of the universal precaution policy on class I inpatient nurses at Hospital X. Informants consisted of nurses from Hospital X including IPCN, class I inpatient nurses, IPCLN ICU rooms, and room leader of class I inpatient rooms. The result of this study is that all informants have understood the purpose of the universal precaution policy at Hospital X, but cannot mention the full policy objectives. Human resources, funds, and facilities at Hospital X have fulfilled the need for implementing universal precaution policies. Communication between implementing parties is good, but there are no sanctions and rewards. The available competencies are sufficient. Supervision in the implementation of this policy is carried out by the KPPI (Infection Prevention and Control Committee) and tiered supervision that has been running well. Class I inpatient nurse at Hospital X has good cognition on universal precaution points. KPPI Hospital X needs to conduct upgrading to refresh the cognition of officers regarding the universal precaution policy. It is necessary to have a separate budget post for KPPI, as well as periodic awards for employees of Hospital X.